Comparative investigation on the supercritical carbon dioxide power cycle for waste heat recovery of gas turbine. (15th January 2021) - Li, Bo; Wang, Shun-sen; Wang, Keke; Song, Liming
Abstract: In this paper, a comparative investigation on the supercritical carbon dioxide power cycle for waste heat recovery of gas turbine is carried out. Four categories and six cycles are chosen to represent typical layout of supercritical carbon dioxide power cycle based on thorough literature reviews. The selected cycles are optimized and analyzed based on the results of single- and multi-objective optimization from the perspective of system efficiency, economic cost and configuration complexity. According to the exergy destruction analysis, several guidelines about the heat exchangers are proposed to enhance the thermal efficiency of gas turbine waste heat recovery system, including the avoiding of preheating, the utilization of partial heating layout, the employment of segmentation method and modified logarithmic mean temperature difference, the increase in the number of gas heater. The results indicate that turbine dominates the investment cost of power cycle. In conclusion, dual heated cascade cycle-II should be employed to pursue the maximized system efficiency. Otherwise, partial heating cycle is recommended due to its balanced overall performance. Highlights: Six cycles are compared based on single- and multi-objective optimization results. Some guidelines about the configuration of heat exchangers are proposed. The cycles are evaluated from thermodynamics, economics and complexity. The partial heating cycle is recommended due to its balanced overall performance.